Blockchain Technology in Electric Vehicle Ecosystems: A Literature Review - Onar, Sezi Cevik; Kahraman, Cengiz; Oztaysi, Basar; Cebi, Selcuk (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
Blockchain enables decentralized, transparent, and secure data management. Due to these advantages using blockchain technologies create new benefits in the electric vehicle (EV) battery ecosystem. In this study, we focus on the literature studies to reveal the usage areas, benefits and drawbacks of blockchain technologies in electric vehicle (EV) battery ecosystem. Scopus database and VOSViewer is used to analyze and map key themes. According to these analysis, four thematic clusters emerged, namely, EV charging, energy trading, second-life battery use, and security. These thematic concepts are further analyzed with in depth analysis. The findings reveal that the blockchain's role is crucial for EV battery ecosystem. By creating trust, transparency, traceability, and automation, blockchain technologies provide various advantages in all these main concepts. Especially, they are very useful for the systems such as digital battery passport and help managing the life cycle of the battery.
Keywords: Blockchain; Electric vehicles; EV; Digital Transformation; Battery management; Charging; Energy trading; Privacy; Literature review; Computer Science